Электронные средства обработки, преобразования и отображения информации - Доля, А. С.; Карнаушенко, В. П. (ХНУРЕ, 2017)
A means of reproducing and displaying information uses a large number of new materials; for their manufacture various technological processes are applied. Recently, display facilities have undergone significant technical changes in connection with the use of electronics, microminiaturization, ergonomics, as well as increased reliability and efficiency of use.
Keywords: Электронные средства обработки; Преобразование информации